THE USE OF POP-UP BOOK TO IMPROVE ENGLISH SKILL AT SD NEGERI 2 GADING KULON DAU - Atin Colidiyah (University of Muhammadiyah Malang, 2018)
This research aims to know the use of pop-up book to improve English skill at SD Negeri 2 Gadingkulon. In this school, most students had low score in English skill because of limited media for teaching English. In this case, the researcher wants to improve English skill by implementing pop-up book for teaching. The subject of this research was second grade students which consist of 15 students. The method used in this study was classroom action research (CAR) in which the researcher worked collaboratively with the teacher. This research applied two cycles with four stages; planning, action, observation, and reflection. The data were taken from field note and scoring rubric. Furthermore, the result of this research was shown pop-up book can enhance students to be active and cooperative in the classroom. Therefore, pop-up book can improve students’ English skill. It was proven by average score in cycle 1 was 70 and cycle 2 was 86. Thus, all the students achieved Minimum Mastery criterion (KKM).